Upaya Meningkatkan Minat Belajar Peserta Didik Melalui Model Problem Based Learning di Sekolah SMKN 1 Guguk - Yanti, Yuni Afri (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to identify the effectiveness of implementing the Problem-Based Learning (PBL) model in improving students’ learning outcomes in Islamic Religious Education (PAI). The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The results show a significant improvement in students’ average scores from cycle I to cycle II, with all students achieving completeness in cycle II, with an average score of 85.3. This learning model is effective in increasing student engagement, understanding of the material, and social skills. Therefore, the PBL model can be an alternative to improve the quality of PAI learning in the classroom manuskrip.